ANALISIS KEBUTUHAN AWAL PENGEMBANGAN DIGITAL INTEGRATED SCIENCE TEST (DIST) BERBASIS HOTS MENGGUNAKAN TAKSONOMI MARZANO PADA SISTEM ORGAN DI SMP NEGERI KOTA PONTIANAK - Rahmawati, Rahmawati; Ariyati, Eka (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
This study aims to analyze the needs for developing a Digital Integrated Science Test (DIST) based on Higher Order Thinking Skills (HOTS) using Marzano's taxonomy in the topic of human organ systems for junior high school students in Pontianak. The research is part of a Research and Development (R&D) approach using the 4D model define, design, develop, and, disseminate. The focus of this article is the define phase, involving front end analysis, learner analysis, task analysis, concept analysis, and specifying instructional objectives. Data were collected through interviews, questionnaires, focus group discussions, and document analysis involving 28 science teachers and 134 eighth grade students from public junior high school in Pontianak. The findings indicate a significant gap between the ideal expectations of the Merdeka Curriculum and the actual implementation of assessments. Most teachers use low order cognitive level questions and have limited knowledge of HOTS and Marzano's taxonomy. However, both teachers and students showed high interest in digital assessments and recognized the human organ system topic as appropriate for HOTS development. These results highlight the urgent need for digital based HOTS instruments that are valid, practical, and relevant to the current curriculum. The study provides foundational insights for the subsequent development stages of the DIST instrument. Keywords: HOTS, Taksonomi Marzano, Digital Integrated Science Test, Sistem organ